PENGARUH TIPE GROUP INVESTIGATION BERBASIS VLOG TERHADAP KEMAMPUAN BERBICARA TEKS BERITA PADA PESERTA DIDIK KELAS XI SMA NEGERI 1 PAGADEN - Windi Nur Hikmah; Irpan Maulana; Desti Kusmayanti (Universitas Hamzanwadi, 2026)
This study looks at how using the group investigation cooperative model, along with making vlogs, affects students’ ability to speak about news texts in Grade XI at SMA Negeri 1 Pagaden. The focus is on how this approach improves students’ confidence, fluency, and vocabulary when they speak out loud. A quasi-experimental design within a quantitative framework was used in this research, with each group consisting of 34 students. The data includes scores from before and after the intervention, N-Gain analysis, and a Mann-Whitney test. The results show that the experimental group improved a lot, with their average score going up from 43.91 to 70.94, and an N-Gain of 0.48, which is considered moderate. The control group had an average posttest score of 58.79 with an N-Gain of 0.24, which is low. The Mann-Whitney test showed a very small significance value of 0.000, which is less than 0.05, meaning there was a significant difference between the two groups. These results show that using the vlog-based group investigation model helps students improve their speaking skills in news texts through working together and practicing creative presentations.